Reuse and disposal and saline drainage water in Haryana, India - van Hoorn J.W.; Boumans J.H.; Kruseman G.P.; Tanwar B.S. (Reuse of low quality water for irrigation, 1989)
A project was carried out in the Haryana State (India) in order to study the future rise of the groundwater level, its agroeconomic consequences and the technical solutions for water table control in which the reuse and disposal of saline drainage water play a major part. A groundwater model was made for the whole state of Haryana, to predict the development of the water table for the next 30 years. This model forecast that approximately 20,000 km2 would be waterlogged after 30 years. An agroeconomic study was done in order to establish a timetable of the agroeconomic deterioration, to identify the areas with the highest losses and to estimate the investment ceiling and the internal rate of return for the technical measures for water table control. The technical solutions and the reuse and disposal of drainage water are discussed in this paper.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)